2017
DOI: 10.18203/2394-6040.ijcmph20170294
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ‘SMART health education model’ on knowledge and attitudes of school students in rural area about ‘Swachh Bharat Abhiyan of India’ and sanitation practices

Abstract: Background: India has been facing various sanitation problems like open defecation, insanitary toilets, improper waste disposal, manual scavenging etc.  Poor sanitation in schools, particularly rural schools are health hazards and affects school attendance, retention and educational performance. Several studies reported poor knowledge about sanitation practices among school students in India, so there is need to inculcate good sanitation practices among them. ‘Swachh Bharat Abhiyan’ is national level health ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…91.30% of the subjects wanted to participate in SBA according to Utpat et al study. 10 Our study found that majority (81.8%) of the literates, compared to illiterates felt that people must actively participate in SBA and this was found to be statistically significant (p=0.005). This could be due to the fact that literates were having better level of understanding regarding objectives of SBA and importance of environmental hygiene.…”
Section: Perception Regarding Sbamentioning
confidence: 54%
See 1 more Smart Citation
“…91.30% of the subjects wanted to participate in SBA according to Utpat et al study. 10 Our study found that majority (81.8%) of the literates, compared to illiterates felt that people must actively participate in SBA and this was found to be statistically significant (p=0.005). This could be due to the fact that literates were having better level of understanding regarding objectives of SBA and importance of environmental hygiene.…”
Section: Perception Regarding Sbamentioning
confidence: 54%
“…9 In another study conducted by Utpat et al in Pune, it was found that 80.43% subjects thought that there is need of SBA and 72.82% felt that SBA is effective. 10 These findings reflects the positive perception of the community towards SBA. Current study revealed that 77.45% of the study subjects thought that all the people must actively participate in SBA activities.…”
Section: Perception Regarding Sbamentioning
confidence: 83%
“…found that 91.30% of the subjects wanted to participate in SBA. [ 9 ] Results of this study showed that majority of the participants agreed with the importance of their participation in SBA activities…”
Section: Discussionmentioning
confidence: 86%
“…He found that 91.30% of students agreed with that their participation is necessary for SBA. [ 9 ] This study showed that the majority of the participants agreed that the contribution at an individual level is important in SBA.…”
Section: Discussionmentioning
confidence: 88%
“…This shows that participants have positive perception of SBA, which is also in consonance with other similar studies done in other states of India. [10]…”
Section: Discussionmentioning
confidence: 99%